2017
DOI: 10.1038/srep45627
|View full text |Cite
|
Sign up to set email alerts
|

Novel conjugates of aminoadamantanes with carbazole derivatives as potential multitarget agents for AD treatment

Abstract: A new group of compounds, promising for the design of original multitarget therapeutic agents for treating neurodegenerative diseases, based on conjugates of aminoadamantane and carbazole derivatives was synthesized and investigated. Compounds of these series were found to interact with a group of targets that play an important role in the development of this type of diseases. First of all, these compounds selectively inhibit butyrylcholinesterase, block NMDA receptors containing NR2B subunits while maintainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 88 publications
1
32
0
Order By: Relevance
“…Hybrids of aminoadamantanes with carbazole and tetrahydrocarbazole ( Figure 6 ) were synthesized and tested as inhibitors of h AChE and equine serum BChE, as antagonists of NMDARs and as stimulators of microtubule assembly [ 47 ]. In AD, microtubule structure disturbance and tubulin polymerization suppression are signs of the incoming neurodegeneration that lead to failures in the axonal transport; therefore, it is necessary to develop compounds that are able to stabilize microtubule structure and to enhance tubulin assembly [ 47 , 48 ].…”
Section: Memantine and Cholinesterase Inhibitor Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrids of aminoadamantanes with carbazole and tetrahydrocarbazole ( Figure 6 ) were synthesized and tested as inhibitors of h AChE and equine serum BChE, as antagonists of NMDARs and as stimulators of microtubule assembly [ 47 ]. In AD, microtubule structure disturbance and tubulin polymerization suppression are signs of the incoming neurodegeneration that lead to failures in the axonal transport; therefore, it is necessary to develop compounds that are able to stabilize microtubule structure and to enhance tubulin assembly [ 47 , 48 ].…”
Section: Memantine and Cholinesterase Inhibitor Hybridsmentioning
confidence: 99%
“…These compounds have a chiral centre, but the binding poses of the two enantiomers are very similar, with the hydroxyl groups that establish hydrogen bonds with different amino acid residues depending on the R or S isomer. Taking into account the position of the entire ligand, it was highlighted that it does not vary when amantadine is replaced by memantine, and a similar behavior is observed with the switch from carbazole to tetrahydrocarbazole; however, when a halogen substituent is inserted, the carbazole core undergoes a flip to reduce the steric strain [ 47 ].…”
Section: Memantine and Cholinesterase Inhibitor Hybridsmentioning
confidence: 99%
“…Early studies performed on patients suffering from AD 7 found an altered cholinergic activity, which resulted in cognitive and functional symptoms. In the present study, we focus our attention on the cholinergic system, which is the most cited potential mechanism 11 , 12 . The cholinergic system directly contributes to regulation and memory process, thus represents a suitable target for the AD drug design 3 , 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The major constituents of the senile plaques are amyloid β (Aβ)‐peptides generally containing 40 or 42 amino acids, which are formed from the proteolytic cleavage of the amyloid precursor protein by α‐ and β‐secretases . There is a large variability in the behavioral changes and time progression of neurodegenerative symptoms among AD patients, reflecting the complex pathology of this disease, which urges the development of efficient therapeutic approaches beyond the current Food and Drug Administration (FDA)‐approved drugs for palliative symptomatic treatments …”
Section: Introductionmentioning
confidence: 99%